Pendampingan Pembuatan Gula Merah Berbahan Nira Batang Kelapa Sawit di Desa Sei Musam, Kecamatan Sei Batang Serangan - Healthy Aldriany Prasetyo; Rafael Remit Winardi; Lyndon Parulian Nainggolan (Universitas Medan Area, 2023)
Community service is carried out as part of the implementation of the Tri Dharma of Higher Education which aims to assist the community in increasing knowledge and skills in the field of making brown sugar that utilizes the sap of palm oil stems. Oil palm stem sap can be processed into brown sugar which is an alternative for processing palm oil waste in Sei Musam Village, Sei Batang Serangan District, Langkat Regency. The method of implementing this community service activity is in the form of assistance to brown sugar producers in the form of technology transfer, management, and equipment support. Assistance activities carried out for 2 (two) days. The result of the mentoring activities is an increase in palm sap processing skills, and an increased understanding of business management, especially in financial governance with simple bookkeeping. Assistance to brown sugar artisans needs to be done considering the quality of brown sugar produced so far is still low and the shape of the brown sugar produced is not uniform. The assistance team provided equipment in the form of a brown sugar molding tool to produce a uniform brown sugar mold so that when it is packaged it looks neat for marketing. From the community service activities that have been carried out, it shows that the craftsmen are able and successful in making brown sugar uniform shapes and are able to calculate the cost of producing brown sugar from palm oil stem sap.